Using Digital Media: Beelinguapp Application to Improve Indonesian Middle School Students' Reading Comprehension Achievement in English - Satria, Budi; Angraini, Nike; Iman, Jaya Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In recent years, integrating digital tools into education has gained momentum, particularly in teaching English as a Foreign Language (EFL). This study investigates the effectiveness of Beelinguapp, a bilingual reading application, in enhancing the reading comprehension skills of middle school learners in Indonesia. A quasi-experimental research design was employed, involving 26 middle school students divided into experimental and control groups. The experimental group used Beelinguapp over six weeks, while the control group followed traditional reading instruction methods. Results reveal a statistically significant improvement in the achievement of reading comprehension in the experimental group. The study underscores the value of leveraging digital tools such as Beelinguapp in EFL classrooms, offering insights into the pedagogical implications of integrating technology to foster engagement, understanding, and motivation in reading activities.